Kebhinekaan Dalam Budaya Perspektif Tafsir Kementerian Agama Republik Indonesia - Maula I.W, Nada; Fariha, Zidna; Nuzulanisa, Kafhaya; Wulandari, Sri Ari (Moderatio: Jurnal Moderasi Beragama, 2023)
This research examines cultural diversity, especially in the Indonesian context. Considering that Indonesia is a nation rich in culture, ethnicity, race and religion, differences are natural. So that cultural diversity in Indonesia is a necessity that cannot be denied. Even in the Qur'an there are several verses that discuss multiculturalism. In this reseach the authors used a descriptive-qualitative method to describe the concept of cultural diversity in the Qur'an and the Indonesian context as well as the interpretation approach of the Indonesian Ministry of Religion's LPMA as a analysis. The result of this research is, in realizing diversity in the context of Indonesia country, the government has an important role to play as a facilitator in maintaining local wisdom.